AN INFLUENCE OF EDUCATION LEVEL, COMPETENCE AND RECRUITMENT PERFORMANCE OF VILLAGE CONSULTANCY BOARDS (BPD) IN PERCUT SEI TUAN, DELI SERDANG DISTRICT - Depi Andrianto; Syaiful Bahri; Hasrudy Tanjung (SEAN Institute, 2022)
Performance is the result of certain work operations carried out in a planned manner in a certained place and at a certained time by employees of the organization concerned. Every company/organization usually has an a expectations the worked assigned to its employees can be completed properly. This case is a very ineffective for the continuity of the company/organization. Because poor performance like this will make it difficult for the company/organization to provide services to consumers or the public for government organizations, which will certainly hurt the company/organization's profits and reputation. One of the supporting factors for employees who can produce good performance is of course inseparable from the role of the level of education, competence, and how the process of receiving (Rekturmen) these employees in the company/organization. Therefore, this study is intended to examine the effect of education level, competence, and recruitment on the performance of the Village Consultative Body in Percut Sei Tuan District, Deli Serdang Regency. The population in this study amounted to 160 people with a sample size of 98 people who became respondents. The results of this study are that the Education Level Variable has a positive and significant effect on the Performance Variable, as well as the Competency Variable has a positive and significant effect on the Performance Variable. Meanwhile, the Recruitment Variables have a positive but insignificant influence on the Performance Variables of the Village Consultative Body in Percut Sei Tuan District, Deli Serdang Regency.